Virtual connections, personal resources, loneliness, and academic self-efficacy among college students with and without LD. Issue 3 (2nd July 2016) - Sharabi, Adi; Sade, Sarit; Margalit, Malka
Abstract: The goals of the study were first to compare the social and academic well-being (loneliness and academic self-efficacy (ASE) among college students with and without learning disabilities (LD), as well as three personal strengths (hope, optimism and sense of coherence (SOC). The second goal was to identify the predicting factors to their loneliness and ASE. The sample consisted of 178 female students from the special education programme in a teachers' college, divided into two subgroups: 59 students with LD and 119 students without LD. The following questionnaires were used: the loneliness scale; ASE; Internet and smartphone activities; hope, optimism and SOC. As expected, students with LD reported higher levels of loneliness and lower levels of ASE. Multiple hierarchical regression analyses showed that the use of the Internet for avoidance coping was a significant predictor for the loneliness and ASE. Results of the mediation analysis further demonstrated that LD was positively associated with online avoidance coping. However, hopeful thinking had a significant mediation effect between LD and online avoidance coping. Students with LD who have hopeful thinking were less engaged in avoidance coping than their peers, focusing attention on the importance of hope as a mediation factor.